Dinuclear planar chiral ferrocenyl gold(i) & gold(ii) complexes. Issue 94 (5th October 2015) - Ayerbe Garcia, Marta; Frey, Wolfgang; Ringenberg, Mark R.; Schwilk, Max; Peters, René
Abstract : The first scalemic ferrocenyl gold(i ) and gold(ii ) complexes have been prepared and structurally analysed by X-ray, (spectro)electrochemical and DFT studies. Abstract : Oxidation of Au(i ) in the presence of Fe(ii ) allowed for the synthesis of unique dinuclear ferrocenyl Au(ii ) complexes via the first reported enantiopure planar chiral ferrocenyl Au(i ) complex. (Spectro)electrochemical studies show that oxidation at Fe(ii ) is favoured, but DFT studies suggest that the energy differences for oxidation of one or the other metal should be quite small.